2021
DOI: 10.1103/physrevd.103.024039
|View full text |Cite
|
Sign up to set email alerts
|

Extending gravitational wave extraction using Weyl characteristic fields

Abstract: We present a detailed methodology for extracting the full set of Newman-Penrose Weyl scalars from numerically generated spacetimes without requiring a tetrad that is completely orthonormal or perfectly aligned to the principal null directions. We also describe how to implement an extrapolation technique for computing the Weyl scalars' contribution at asymptotic null infinity in postprocessing. These methods have been used to produce Ψ 4 and h waveforms for the Simulating eXtreme Spacetimes (SXS) waveform catal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 56 publications
0
36
0
Order By: Relevance
“…Each simulation contains roughly 19 orbits prior to merger and is evolved until the waves from ringdown leave the computational domain. Unlike the evolutions in the SXS catalog, the full set of Weyl scalars and the strain have been extracted from these runs, and the waveforms have been computed using the extrapolation technique described in [24] and the CCE procedure described in [25,37]. Extrapolation is performed with the PYTHON module SCRI [13,[28][29][30] and CCE is run with SpECTRE's CCE module [25,37,38].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each simulation contains roughly 19 orbits prior to merger and is evolved until the waves from ringdown leave the computational domain. Unlike the evolutions in the SXS catalog, the full set of Weyl scalars and the strain have been extracted from these runs, and the waveforms have been computed using the extrapolation technique described in [24] and the CCE procedure described in [25,37]. Extrapolation is performed with the PYTHON module SCRI [13,[28][29][30] and CCE is run with SpECTRE's CCE module [25,37,38].…”
Section: Resultsmentioning
confidence: 99%
“…We set c ¼ G ¼ 1 and take η μν to be the ð−; þ; þ; þÞ Minkowski metric. When working with complex dyads, following the work of [24], we use…”
Section: B Conventionsmentioning
confidence: 99%
“…As such, it is not expected that a velocity measured with respect to some local coordinates will be comparable to that same velocity measured with respect to an entirely different coordinate system set up on I þ . In fact, it has been shown that the naive choice of retarded time u ¼ t − r à in simulation coordinates (where r à is the radial tortoise coordinate) actually fails to parametrize null rays for BBH spacetimes [46,89].…”
Section: B Recoil Velocity Comparisonmentioning
confidence: 99%
“…Recent developments have established reliable procedures for computing the gravitational-wave strain h and the Weyl scalars ðψ 4 ; ψ 3 ; ψ 2 ; ψ 1 ; ψ 0 Þ at I þ from an NR simulation [44][45][46]. These asymptotic quantities, collectively known as Bondi data or asymptotic data, are subject to an infinitedimensional group of gauge freedoms described by the Bondi-Metzner-Sachs (BMS) group [47,48], which is an enlargement of the Poincaré group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation